Pengaruh Perbaikan dan Penggunaan Variasi Persentase Elektrolit Terhadap Daya dan Ketahanan Lead Acid Battery Bekas Tipe NS40 - Dava Alifiano; Khambali Khambali (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
The amount of load on the vehicle requires a balance current and voltage. To fullfill the requirement, vehicle use a energy stroage media called lead acid battery. Although the lead acid battery have a impaccable durability, the performance will be decrase as long as use, especially in term of power and durability. The downgrade performance from the battery make high cost replacement, meanwhile there is a change to fix the battery. One of the methode to fix is replace the cell and added H₂SO₄ electrolyte concentrat variation. This research intend to examine repairment effectivity and electrolyte concentrat variation on power for used lead acid battery NS40 type. H₂SO₄ electrolyte that used is 30%,40% and 45% examine with 5 static dummy load 1 Ω 100 W pararrel circuit. Each electrolyte examine 60 times to obtain performance and durability data. The results show that increasing the concentration of H₂SO₄ has a significant effect to produce the voltage and current. At 30% concentrate, an average voltage is 9.8 V and the current is 30.125 A at 40% concentarte, the voltage is 10.18 V and the current is 32.731 A and at 45% concentrate, the voltage is 10.19 V and the current 33.375 A.